The demand for welfare institutions in refugee camps - Bhuiyan, Md. Mahmudur Rahman (Frontiers in Human Dynamics, 2024)
Long-term encampment has become a reality for a large portion of the forcibly displaced population of the contemporary world, given the inadequacies and limitations of the conventional durable solutions to forced displacement. However, encampment is principally a temporary arrangement that prevents long-term programming in camps, making long-term encampment contradictory and an arena of uncertainty, misery, and despair for the camp dwellers. It is rather more rational to admit long-term encampment as a reality and act on it as it involves unjustifiable humanitarian costs. The paper calls for thinking beyond the conventional practices and focusing on the wellbeing of the encamped population from a life-course perspective. It proposes a framework for building welfare institutions in refugee camps.